Pembelajaran inkuiri terbimbing dalam pembelajaran matematika untuk meningkatkan kemampuan penalaran matematis siswa SMP - Abdul Jabar (STKIP PGRI Banjarmasin, 2018)
Mathematics learning in schools today is still limited as a process of delivering knowledge about mathematics. On the other hand, the assumption that mathematics is a difficult subject causes students to be lazy to learn mathematics and the low involvement of students in the learning process To give more opportunities for students to actively learn now developing models of learning. One of the guided Inquiry learning models that can make students active in solving problems. The purpose of this research is to know the students' mathematical reasoning ability in rectangular material in class VIIC SMP Negeri 2 Kandangan 2016/2017 lesson year with Guided Inquiry learning model. This study was conducted using classroom action research (PTK) in 2 cycles with 6 meetings. The subjects of this study were students of class VIIC SMP Negeri 2 Kandangan with the number of students 25 people consisting of 15 men and 10 women, and objects in this study the ability of mathematical reasoning, data collection techniques used tests. Technique of data analysis in this research use mean value and percentage.Research result in quadrilateral study by using Guided Inquiry model on class VIIC student of SMP Negeri 2 Kandangan show student's mathematical reasoning ability increase from qualification enough in cycle I become qualification well once in cycle II.